Analisis Penentuan Harga Jual dengan Metode Cost Plus Pricing pada UD Bintang Kejora - Herminaini Mauris Khoirunnisa; Abu Darim (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to analyze the determination of the selling price using the cost plus pricing method at UD Bintang Kejora. This type of research uses case research which is selected based on the formulation of the problem and research objectives. The data collection technique used is documentation. Data analysis techniques used are data collection, data reduction, data presentation and conclusion. The data validity technique used is source triangulation.The results of the study show that UD Bintang Kejora in determining the cost of production is still not in its entirety, such as not including maintenance costs and depreciation of equipment used in the production process. Therefore, researchers calculate the cost of production using the full costing method and determining the selling price of the cost-plus pricing method to help companies get the appropriate profit. The cost of production using the full costing method is Rp. 44,455. The profit obtained by adding a margin of 35% of the cost of production is Rp. 15,559. In order to obtain a selling price using the cost-plus pricing method of Rp. 60,014. The results of the calculation of determining the selling price with this method can help UD Bintang Kejora in getting the desired profit.